Hubungan pendidikan ibu hamil terhadap persepsi mutu pelayanan pada kunjungan pelayanan antenatal care - Umi Khasanah (Universitas Muhammadiyah Semarang, 2020)
Integrated Antenatal Care is a comprehensive and quality antenatal service for all pregnant women provided by trained and professional medical personnel. Providing quality services and services needed by pregnant women will make the perception of pregnant women about Antenatal Care services better. The purpose of this study was to analyze the relationship of education of pregnant women to the perception of service quality at Antenatal Care service visits in the Surakarta Region Health Center. This quantitative research method uses a cross-sectional approach with an accidental sampling technique in sampling so that as many as 108 respondents obtained then the data analysis uses chi-square. The results of this study most of the highly educated pregnant women expressed a good perception about the quality of Antenatal Care Services in the Surakarta Region Health Center. The conclusion of the study is that there is a relationship between the level of education of pregnant women with the perception of service quality at Antenatal Care visits with a p-value of 0.027. The p-value is smaller than 0.05 (0.027 <0.05). Improving the level of education in the community needs to be done so that pregnant women are more understanding and critical about services provided during Antenatal Care visits.